Sawing Optimisation for Block Panel's Production of Portuguese West Littoral Maritime Pine Radial Boards - Campos,José (2001)
Increasing wood demand as raw material and the necessity to adjust each end use to the characteristics and properties of each wood has been improving the employ of round wood of small dimensions as well as low quality sawn wood. In this case we may include radial boards and the two adjacent tangential boards, even if obtained from large round wood. The available technological processes, mostly based on the identification and location of one of the most important wood defects - the knots - tend to maximize the utilisation level of small wood so as to improve quality and productivity. Maritime pine radial boards are the worst sawn pieces concerning presence of knots on more or less distant whorls along the stem. However, although being an unfavourable characteristic of the species, knot concentration on bands, separated by long annual height growth, allows the utilization of board wood in between. This paper aims to estimate mean values of number, size, location, condition and shape of knots on a sample of 161 radial boards from 38 maritime pine trees, collected in three pine forests located along the Portuguese littoral west coast. Based upon data collected in the stand and in the sawmill, it's also simulated the optimization of clean wood for sawing, in order to produce block board panels. To simulate lath profit, was taken account of tree provenance, statute in the stand, dbh, board mean diameter, number of knot bands and log ranking in the tree. The lath dimensions usually utilized by block boards panels industry were considered.